Child-Raising in African Context: The Urhobo Perspective - Oghenenyerhovwome Watson Olonge (International Journal of Religion, Humanity and Cultural Heritage, 2025)
The challenge of raising a child holistically to meet societal standard is becoming difficult in the 21st century and this poses a great concern for social and cultural stability, a situation were there seem to be moral and ethical decay. This paper seeks to present the African way of raising the child as a model to curb the growing challenges in parenting. This will however be discussed within the Urhobo cultural perspective.  Thus the aim of this paper is to showcase some of the Urhobo ways of child raising  as a model for enhancing a fairly balance moral society. The historical and phenomenological approaches were adopted. The research discovered that foreign cultural practices poses existential challengesto the Urhobo and African cultural heritages.  Also it discovered that there is the abandonment of cultural discipline, culture of hard-work, societal norms and values to adoption of western culture. The paper concludes that proper parenting and child-raising is cardinal to having a better future and society. Our cultural and traditional institutions should be the basis to enhancing this process. The study recommends that parents,  society and government should take child-raising a priority and see to it that cultural values and heritage are instill in the Urhobo children.